Analisis Kuantitatif Kandungan Antioksidan dan Aktivitas Sitotoksik dari Ekstrak Anastatica hierochuntica L - Nova Lusiana; Risa Purnamasari; Eva Agustina; Nurul Ilmi Faidah; Azlinda Mitha Agustin; Muhammad Falikhul M (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
Antioxidants are compounds that can counteract free radicals in the body due to the presence of active compounds such as flavonoids and phenolics. These active compounds can be cytotoxic, ie, compounds capable of inhibiting and stopping the growth of cancer cells by using toxicity test by BSLT (Brine Shrimp Lethality Test) method. This study aims to determine the antioxidant activity by DPPH (Dipheny Pycryl Hydrazil) method and toxicity test by BSLT method of Anastatica hierochuntica L extract. A. hierochuntica L extraction were done by maceration method with methanol solvent. The content of A. hierochuntica L extract compounds was done by phytochemical test to know flavonoid compounds, triterpenoid and sterol. Meanwhile, alkaloid and saponin and liquid chromatography to see flavonoid compounds of quersetin. Furthermore, the antioxidant activity test was carry out by the DPPH method and by BSLT method to observed the mortality of shrimp larvae. A. hierochuntica extract has antioxidant activity with IC50 value 77,23 μg / ml and toxicity value of LC50 44,97. A.hierochuntica L extracts potentially have antioxidant and cytotoxic properties.